Η διαχρονική αντίληψη της Αιγύπτου μέσα από τις λογοτεχνικές πηγές της κλασικής αρχαιότητας - Χατζηπέτρου, Βασιλική (2021)
It is a noticeable fact that Greek poets always seem to make a reference to Egypt in their work, not to mention Euripides’ Helen, where the drama actually takes place in Egypt. It may be a simple reference to their everyday routine or its customs which might be causing turmoil to the Greek city-states. However the question remains, is the depiction of Egypt an accurate one or a distorted one? In these plays, is Egypt depicted as a remote historical site based on unreliable and fragmentary information or do we actually have trustworthy data on historical Egypt? Is the Egypt portrayed in the classical Greek tragedy of the 5th century B.C Athens a historical reality or not? The Greeks were fascinated with the Egyptians for years. Greek literature and art of the classical period are especially thick with representations of Egypt and Egyptians. Yet despite numerous firsthand contacts with Egypt, Greek writers constructed their own Egypt, one that reflected their own attitudes and prejudices. There is an extensive reference to Egypt in Herodotus’ second Book, Euterpe. Whilst details of his account have been challenged, his preeminence as the inventor of the methodology and philosophy of history are undisputed. Therefore, in the History of Herodotus, one may understand how the Greeks most probably viewed Egypt and the Egyptians, as he extensively refers to the country and its customs. It is a fact that the two countries were in contact from the 7th century B.C., however Herodotus is unquestionably considered a significant source of information on the Greeks’ perception of the Egyptians in the Classic era. A play with reference to Egypt is Aeschylus’ “The Suppliants” which is the only surviving part of a tragic trilogy, Suppliants, Egyptians and Danaids, with the central theme being the fate of the daughters of Danaus. In the Suppliants, Aeschylus explores the intricate link of what is Greek and what is not. What could be considered barbaric and what could not. One notices that in the “Persians”, Aeschylus perceives the ultimate “kinship” between Greek and barbarian. In the Suppliants the poet expands this theme and presents it in a somewhat intense manner. In this later play, which is now generally accepted to have been produced in the late 460s, despite the archaic elements, Aeschylus is more actively interested in how “kinship” both converges and interrelates with cultural polarity, and at the same time undermines and perplexes “otherness”. In Euripides’ Helen the first and foremost noticeable fact is Helen’s supplication which is undeniably “Greek”. The absence of an altar outside the palace is attributed to the barbarian customs according to Menelaus, however Helen later declares that the tomb will do, just as an altar or a temple in Greece would. It thus seems that according to the playwright, Egypt has similar customs with Greece, though somewhat a little different, as is the act of supplication or the case of the burial in the sea. There are of course a number of elements which depict the projection of Euripides’ way of thinking in this play. There is the description of a religious ceremony, with blazing torches and a ritual of purification, according to sacred laws, which is clearly “Greek” and has nothing to do with the Egyptian beliefs. To conclude, it is obvious that in Greek tragedy, Egypt was used as that which is “different”, not necessarily “barbaric”, and therefore not considered inferior or even frowned upon. Simply different to that which the Athenians were accustomed to, and accustomed to being exposed to on stage.